Ravindranath Tagore rachnavali/ Nauka doobi - Tagore, Ravindra Nath; Edited by Indra Nath Chaudhury (New Delhi Sasta Sahitya Mandal, 2021)
Nauka Doobi
Keywords: Hindi novel; Noble prize winner Ravindra Nath Tagore